2018
DOI: 10.1371/journal.pntd.0006339
|View full text |Cite
|
Sign up to set email alerts
|

Model-based inference from multiple dose, time course data reveals Wolbachia effects on infection profiles of type 1 dengue virus in Aedes aegypti

Abstract: Infection is a complex and dynamic process involving a population of invading microbes, the host and its responses, aimed at controlling the situation. Depending on the purpose and level of organization, infection at the organism level can be described by a process as simple as a coin toss, or as complex as a multi-factorial dynamic model; the former, for instance, may be adequate as a component of a population model, while the latter is necessary for a thorough description of the process beginning with a chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Meanwhile, despite being based on low numbers and small effect sizes, the consistency of higher infected proportions among Wolbachia carriers at low challenge doses is noticeable. Ant et al 4 finalise their inspection into the Souto-Maior et al 1 dataset by noting a slight discrepancy between the raw data and the proportions infected shown in Fig. 1a of King et al 3 .…”
Section: Openmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, despite being based on low numbers and small effect sizes, the consistency of higher infected proportions among Wolbachia carriers at low challenge doses is noticeable. Ant et al 4 finalise their inspection into the Souto-Maior et al 1 dataset by noting a slight discrepancy between the raw data and the proportions infected shown in Fig. 1a of King et al 3 .…”
Section: Openmentioning
confidence: 99%
“…They highlight that a fraction of the mosquitoes assigned as infected by dengue may be false positives, without which the increased mean susceptibility of the Wolbachia-carrying group inferred from the dose-response model might not be found, making our reported conclusions appear as an artefact of the analysis. They criticise Souto-Maior et al 1 based on the observation that a small number of negative control mosquitoes were classified as positive, a shortcoming of the original experimental study which neither affects the type of analyses conducted therein nor does it influence the conclusions of King et al 3 , as per modified analysis suggested by Ant et al 4 (Fig. 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…w MelPop demonstrated almost complete blocking of transmission of dengue viruses but also high fitness costs and failed to establish in target field populations [ 52 ]. w Mel shows partial blocking of dengue viruses in the laboratory (but see [ 54 , 55 ]) with lower fitness costs and in trials in Australia established and slowly spread from two of three release sites [ 53 , 56 ] ( Table 1 .)…”
Section: Wolbachiamentioning
confidence: 99%